PEMANFAATAN MATLAB UNTUK PENENTUAN JALUR TERPENDEK EVAKUASI BENCANA TSUNAMI DI WILAYAH KECAMATAN CILACAP SELATAN - Sugeng Dwi Riyanto; Artdhita Fajar Pratiwi; Rostika Listyaningrum (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2020)
The South Cilacap district is one of the area in Cilacap regency with the highest population density and the most prone area of tsunami disaster. Unfortunately, most of the main roads in South Cilacap district is parallel to the coastline. This condition will slow down the evacuation of residents to safe locations. In 2006 and 2017, Cilacap regency has experienced several earthquake that have a potential of a tsunami. It caused people to panic and tended to choose the evacuation route through the main roads without considering the route became congested and resulted in total congestion. Based on these conditions, a system that contains information about the shortest evacuation route that should be taken by the residents to a safe location is needed. The shortest evacuation route is determined using MATLAB software. The simulations was creating on MATLAB, there is a starting vertexes as a starting location or location of a tsunami prone area and a finish vertexes as a destination location or a safe location from a tsunami disaster. By using MATLAB software, it can simulate the shortest path for tsunami evacuation in the South Cilacap district area along with the distance and graphic images.